The Green Man - Hutton, Ronald (Journal for the Study of Religion, Nature and Culture, 2023)
The Green Man, a figure usually taken as representing the vivifying and fertilising power of the natural world, and especially of vegetation, has become one of the icons of modern ecology and environmental spirituality. He is often represented visually by a foliate head, gushing leaves from mouth and nose, of the kind found carved in medieval churches, and associated also with the foliate Jack-in-the-Green character in May Day festivities and with dying and returning fertility gods in ancient mythologies. This essay is intended to chart the development of the figure, which gains much of its emotive and creative power from being a twentieth-century construction, drawing on a range of disparate older images. It provides an important case study of the relationship between professional and independent scholarship in the creation of modern ideas, and the manner in which new and powerful iconic motifs can be evolved within modern spirituality.